Racial disparities in age at preventable hospitalization among U.S. Adults. - Biello, Katie Brooks; Rawlings, James; Carroll-Scott, Amy; Browne, Rosa; Ickovics, Jeannette R (American journal of preventive medicine, 2010)
Similar to the well-documented racial inequities in health status, disease burden, healthcare access, and hospitalization, studies have generally found higher rates of hospitalization resulting from ambulatory care-sensitive conditions for blacks compared to whites. Beyond identifying disparity in rates of disease or risks of hospitalization, identifying disparity in age at hospitalization may provide deeper insight into the social and economic effects of disparities on individuals, families, and communities.
Keywords: Adolescent; Adult; African Americans; Aged; Ambulatory Care; Demography; European Continental Ancestry Group; Female; Health Care Surveys; Healthcare Disparities; Hospitalization; Humans; Male; Middle Aged; Social Class; United States; Young Adult